Optimal Procurement Contracts with Pre-Project Planning - Daniel Krähmer; Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
The paper studies procurement contracts with pre-project investigations in the presence of adverse selection and moral hazard. To model the procurer's roblem, we extend a standard sequential screening model to endogenous information acquisition with moral hazard. The optimal contract displays systematic distortions in information acquisition. Due to a rent effect, adverse selection induces too much information acquisition to prevent cost overruns and too little information acquisition to prevent false project cancelations. Moral hazard mitigates the distortions related to cost overruns yet exacerbates those related to false negatives. The optimal mechanism is a menu of option contracts that achieves the dual goal of providing incentives for information acquisition and truthful information revelation.
urn:nbn:de:bvb:19-epub-13251-3
Keywords: D82; H57; 330; Information acquisition; procurement; dynamic mechanism design; Beschaffung; Vertrag; Informationsversorgung; Asymmetrische Information; Moral Hazard; Prinzipal-Agent-Theorie; Mechanismus-Design-Theorie; Theorie